Respon Pertumbuhan Vegetatif Tanaman Buncis (Phaseolus vulgaris L.) Dengan Pemberian Kompos Limbah Kulit Pisang Nipah - Mukarlina, Ernawati, Elvi Rusmiyanto Pancaning Wardoyo, (Jurnal Protobiont, 2018)
Bean (Phaseolus vulgaris L.) is a type of legumes from leguminoceae familly which is beneficial to decrease blood pressure and control body metabolism system. Bean can grow well on rich soil which contains much humus. This research aims at identifying the effect of Nipah banana’s skin waste towards the vegetative growth of bean. The research was conducted for thee months since Febuary to April 2017. It was carried out in a lab of biology deapartment, Faculty of Mathematics and Natural Sciences, Tanjungpura Universty. The research employed completely randomized design ( RAL). It consisted of six level of concentration, such as control (P0) 0 (P1) 12.5 (P2) 25 (P3) 37.5 (P4) 50 (P5) 62.5g. They ware carried out with three repetitions so they could gather 18 experimental units. Providing bean with the banana’s skin waste could give a clear effect towards the plant’s heights, gross weight, and dry weight. Using the banana’s skin waste whice has 50g concentration provides the best resulty for the plant’s height (141.30 cm), the number of leaf (37.67 leaves), and dry weight (12.54 g).